Research on antimicrobial resistance in the last 15 years, India: A bibliometric analysis - Shikha Yadav; Mayank Sharma; Kavita Rajesh; Vibhor Dudhraj; Shailja Anand; Suneet Kaur; Arti Bahl (Wolters Kluwer Medknow Publications, 2023)
Effective antimicrobials play an important element in modern medicine's success in treating infections, without which the patients would be put at risk. Along with the naturally occurring process of antibiotic resistance, the misuse/overuse of these antibiotics also leads to them losing their effectiveness. It limits the treatment options as the microbe that had previously been sensitive becomes resistant. This bibliometric study was performed by searching the Scopus database according to a specific search strategy. A total of 4200 articles were retrieved from the search, and after applying inclusion and exclusion criteria, 1355 articles were included in the study. All of the bibliometric variables examined in this study revealed significant growth in this research field, especially during COVID-19, in terms of increasing scientific output and research collaboration. The study findings indicate an adequate quality and amount of antimicrobial resistance (AMR) research on microbiology and pharmacodynamics in India, whereas more research needs to be conducted on measures to tackle AMR, its public health, and policy aspects.